How mixed relay teams in swimming should be organized for international championship success - Veiga, S.; Santos del Cerro, J.; Rodriguez, L.; Trinidad, A.; González-Ravé, J. M. (Frontiers in Psychology, 2021)
The primary goal of the present research was to determine the order of swimmers on a mixed relay team that would ensure the best performance in the Fédération Internationale de Natation (FINA) World Championships held in Kazan (Russia, 2015), Budapest (Hungary, 2017), and Gwangju (South Korea, 2019). The data were obtained from database websites for the 4 × 100 m freestyle and 4 × 100 m medley official results,1 including 660 records from 188 entries of finals and 472 preliminary events. The results showed that the fastest swimmers (according to their best season times) were located primarily in the first or second positions of the freestyle relay. The most successful gender strategy for the 4 × 100 m freestyle (57 out of 82 observations) and for the 4 × 100 m medley (29 out of 83) relays was the order male-male-female-female, although no statistical differences were found (p = 0.79) for the medley relays. In the 4 × 100 m freestyle, the second (p = 0.002; ß = 1.62) and third (p =0.003; ß = 1.41) relay legs had a statistical effect on the total relay time, whereas in the 4 × 100 m medley, all four relay legs had a statistical effect (p < 0.001) on the final performance, the weight of the four strokes being different in heats with respect to the final round. Also, a later position of the first female swimmer or the consecutive position of two female swimmers in the team order significantly affected the relay performance in specific events. Mixed relay events appeared to present specific strategies in comparison to traditional male- or female-only relay lineups.